1996
DOI: 10.1086/mre.11.2.42629148
|View full text |Cite
|
Sign up to set email alerts
|

Effort Dynamics and Alternative Management Policies for the Small Pelagic Fisheries of Northwest Peninsular Malaysia

Abstract: The dynamics of fish stocks are an important consideration in determining appropriate fishery management policy. Equally crucial are the dynamics of fishing effort. Both these dynamics have been incorporated in a simulation model to analyze the bio-socioeconomic impacts of four alternative limited entry management policies for the multispecies, multigear small pelagic fishery of northwest Peninsular Malaysia. Fishing effort dynamics are determined by the difference in profits and opportunity costs. Several man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Considering the complexity of a fishery system, simulation models can be built incorporating both fish population dynamics and fishing effort dynamics. Yew and Heaps (1996), for example, developed a model incorporating bio‐socioeconomic effects of alternative management policies for a small pelagic fishery in north‐west peninsular Malaysia. They showed that the existing policy of limited entry licensing would not achieve the expected outcome as fishers could increase effort by fishing more days or by ‘capital stuffing’ their vessels.…”
Section: Applications In Fisheries Assessment and Managementmentioning
confidence: 99%
“…Considering the complexity of a fishery system, simulation models can be built incorporating both fish population dynamics and fishing effort dynamics. Yew and Heaps (1996), for example, developed a model incorporating bio‐socioeconomic effects of alternative management policies for a small pelagic fishery in north‐west peninsular Malaysia. They showed that the existing policy of limited entry licensing would not achieve the expected outcome as fishers could increase effort by fishing more days or by ‘capital stuffing’ their vessels.…”
Section: Applications In Fisheries Assessment and Managementmentioning
confidence: 99%
“…This is in part due to relative ease of data collection; catch data can be collected at ports or landing sites. While catch data provides important information on the number of individuals harvested, it does not provide information on the expended effort, including details on gear, capital and labour used to harvest stocks (Yew and Heaps 1996). The amount and types of resources devoted to fishing is directly related to the harvesting capacity of the fleet (Kirkley et al.…”
Section: Introductionmentioning
confidence: 99%
“…As applied in the existing studies, the sustainable yield function of the fishery (Y) according to the level of fishing gear usage (E) can be expressed by the yield–effort function of the Schaefer model as shown in : 3–6 …”
Section: Methodsmentioning
confidence: 99%